2015
DOI: 10.1111/bjd.14158
|View full text |Cite
|
Sign up to set email alerts
|

CARD14 alterations in Tunisian patients with psoriasis and further characterization in European cohorts

Abstract: Summary Background Rare highly penetrant gain of function mutations in caspase recruitment domain family, member 14 (CARD14) can lead to psoriasis, a chronic inflammatory disease of the skin and other organs. Objectives To investigate the contribution of rare CARD14 variants to psoriasis in the Tunisian population and expand knowledge of CARD14 variants in the European population. Methods CARD14 coding exons were re-sequenced in psoriasis cases and controls from Tunisia and Europe including included sixte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 24 publications
1
44
1
Order By: Relevance
“…Since then, several studies have reported associations of CARD14 variants with psoriasis vulgaris, psoriatic arthritis, generalized pustular psoriasis, and palmoplantar pustular psoriasis (Ammar et al, 2013(Ammar et al, , 2016Eskin-Schwartz et al, 2016;Feng et al, 2016;Gonzalez-Lara et al, 2013;Inoue et al, 2016;Korber et al, 2013;Mossner et al, 2015;Qin et al, 2014;Sugiura et al, 2014Sugiura et al, , 2015Zhu et al, 2016). Furthermore, CARD14 variants have also been associated with pityriasis rubra pilaris, a distinct inflammatory skin disease characterized by keratotic follicular papules and salmon-colored erythematous plaques (Eytan et al, 2014;Fuchs-Telem et al, 2012;Has et al, 2016;Inoue et al, 2016;Li et al, 2015).…”
Section: Card14 Variants In Psoriasismentioning
confidence: 99%
See 2 more Smart Citations
“…Since then, several studies have reported associations of CARD14 variants with psoriasis vulgaris, psoriatic arthritis, generalized pustular psoriasis, and palmoplantar pustular psoriasis (Ammar et al, 2013(Ammar et al, , 2016Eskin-Schwartz et al, 2016;Feng et al, 2016;Gonzalez-Lara et al, 2013;Inoue et al, 2016;Korber et al, 2013;Mossner et al, 2015;Qin et al, 2014;Sugiura et al, 2014Sugiura et al, , 2015Zhu et al, 2016). Furthermore, CARD14 variants have also been associated with pityriasis rubra pilaris, a distinct inflammatory skin disease characterized by keratotic follicular papules and salmon-colored erythematous plaques (Eytan et al, 2014;Fuchs-Telem et al, 2012;Has et al, 2016;Inoue et al, 2016;Li et al, 2015).…”
Section: Card14 Variants In Psoriasismentioning
confidence: 99%
“…However, not all CARD14 variants that have been identified in patients with psoriasis and pityriasis rubra pilaris lead to excessive NF-kB activation. For instance, the variant p.Arg69Trp reduces NF-kB activation sevenfold compared with wild-type CARD14 (Ammar et al, 2016). These ambiguous effects on NF-kB suggest that CARD14 could be involved in additional signaling pathways or that basal NF-kB levels might be crucial to preserve skin homeostasis.…”
Section: Card14 Variants In Psoriasismentioning
confidence: 99%
See 1 more Smart Citation
“…The skin disease in patients with CARD14 mutations can be limited or generalized. Autosomal dominant or sporadic gain-of-function mutations in the CARD14 gene cause GPP (101), familial pityriasis rubra pilaris (PRP) (102), psoriatic arthritis (PA) (103), PPP (104), and even pustular psoriasis suggesting a large disease severity spectrum. Fever and other systemic manifestations are generally not present but can occur with superinfections of the skin.…”
Section: Introductionmentioning
confidence: 99%
“…One Tunisian patient was reported with a c.1356+5G>A splice alteration which is predicted to lead to the skipping of exon 9, which encodes part of the coiled-coil domain (105). Mutations in CARD14 , including p.Glu138del and p.Leu156Pro, have been associated with autosomal-dominant pityriasis rubra pilaris, which is phenotypically related to psoriasis (102). …”
Section: Introductionmentioning
confidence: 99%